Image-guided focused ultrasound: state of the technology and the challenges that lie ahead. (August 2013) - Foley, Jessica L; Eames, Matt; Snell, John; Hananel, Arik; Kassell, Neal; Aubry, Jean-Francois
Image-guided focused ultrasound (FUS) is a noninvasive therapeutic technology platform that results from the marriage of FUS therapy and MR or ultrasound imaging. The thermal and mechanical mechanisms of ultrasound interaction with targeted tissue can produce a variety of localized biological effects that enable the treatment of a wide range of clinical conditions, from uterine fibroids to prostate and liver cancer, to neurological disorders. Coupling FUS therapy with either MR or ultrasound imaging enables precise targeting, planning, monitoring and confirmation of the treatment in real time. Future challenges remain to enable full clinical adoption of image-guided FUS. These include technical advancements to expand the FUS treatment envelope, accumulation of clinical evidence, insurance reimbursement and physician adoption.